Attenuated measles virus used as an oncolytic virus activates myeloid and plasmacytoid dendritic cells - Fonteneau, Jean-François (Landes Bioscience, 2013)
Attenuated measles viruses (MV) are assessed in clinical trials for their capacity to preferentially infect and kill tumor cells. We recently showed that MV-infected tumor cells are able to activate tumor antigen cross-presentation by myeloid and plasmacytoid dendritic cells. Thus, MV-based antitumor virotherapy may stimulate antitumor immune response.